172k views
2 votes
9x - 4 -6x = 2(x + 1) -5
solve for x and show work, please.

User Jurasic
by
5.8k points

1 Answer

1 vote

Answer:

x = 1

Explanation:

Subtract the right side of the equation and simplify:

9x -4 -6x -2(x +1) +5 = 0

9x -6x -2x -4 -2 +5 = 0 . . . . . eliminate parentheses

x -1 = 0 . . . . . . . . . . . . . . . . . . collect terms

x = 1 . . . . . . . . . . . . . . . . . . . . . add the opposite of the constant

_____

Check

Substitute the value of x where x is found in the equation.

9·1 -4 -6·1 = 2(1 +1) -5

9 - 4 - 6 = 2·2 -5

-1 = 4 -5 . . . . . true. The answer checks OK.

User Vladimir Danilov
by
5.2k points